Assessing patient characteristics and radiation-induced non-targeted effects in vivo for high dose-rate (HDR) brachytherapy. (3rd October 2015) - Pinho, Christine; Timotin, Emilia; Wong, Raimond; Sur, Ranjan K.; Hayward, Joseph E.; Farrell, Thomas J.; Seymour, Colin; Mothersill, Carmel
Abstract : Purpose : To test whether blood, urine, and tissue based colony-forming assays are a useful clinical detection tool for assessing fractionated treatment responses and non-targeted radiation effects in bystander cells. Materials and methods : To assess patients' responses to radiation treatments, blood serum, urine, and an esophagus explant-based in vivo colony-forming assay were used from oesophageal carcinoma patients. These patients underwent three fractions of high dose rate (HDR) intraluminal brachytherapy (ILBT). Results : Human keratinocyte reporters exposed to blood sera taken after the third fraction of brachytherapy had a significant increase in cloning efficiency compared to baseline samples ( p < 0.001). Such results may suggest an induced radioresistance response in bystander cells. The data also revealed a clear inverse dose-rate effect during late treatment fractions for the blood sera data only. Patient characteristics such as gender had no statistically significant effect ( p > 0.05). Large variability was observed among the patients' tissue samples, these colony-forming assays showed no significant changes throughout fractionated brachytherapy ( p > 0.05). Conclusion : Large inter-patient variability was found in the urine and tissue based assays, so these techniques were discontinued. However, the simple blood-based assay had much less variability. This technique may have future applications as a biological dosimeter to predict treatment outcome and assess non-targeted radiation effects.